2011
DOI: 10.1111/j.1524-4725.2011.01915.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Syringoma Using an Ablative 10,600-nm Carbon Dioxide Fractional Laser: A Prospective Analysis of 35 Patients

Abstract: The use of CO(2) FS can have a positive therapeutic effect on periorbital syringomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 19 publications
1
22
0
1
Order By: Relevance
“…In a previous investigation, we demonstrated that CO 2 fractional lasers offered positive therapeutic effects in 35 Korean patients with periorbital syringomas (6). In our study, two sessions of CO 2 fractional laser treatment at one-month intervals with the laser settings of a pulse energy of 100 mJ and a density of 200-300 spots/cm 2 resulted in marked to near-total clinical improvement in 51.5% of the participants (6).…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…In a previous investigation, we demonstrated that CO 2 fractional lasers offered positive therapeutic effects in 35 Korean patients with periorbital syringomas (6). In our study, two sessions of CO 2 fractional laser treatment at one-month intervals with the laser settings of a pulse energy of 100 mJ and a density of 200-300 spots/cm 2 resulted in marked to near-total clinical improvement in 51.5% of the participants (6).…”
Section: Introductionmentioning
confidence: 63%
“…Therefore, to more safely deliver higher pulse energy to a larger area, CO 2 lasers with fractional irradiation technology have been used (10). however, as shown in our previous study, the percent coverage of CO 2 fractional lasers was usually limited to 10-30% of the treated area; moreover, improvement scores seemed to decrease with time after CO 2 fractional laser treatment alone, necessitating repeated treatments to achieve satisfactory outcomes in patients with refractory syringoma lesions (6).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Syringomas are eccrine benign tumors of skin occurring A B [16] * BoTN -Botulinum toxin most frequently in the head and neck area. As suggested by our own experience, fractional CO 2 laser may be an effective and safe tool to improve facial appearance for the treatment of multiple periocular syringomas that poorly respond to ablative CO 2 laser.…”
Section: Resultsmentioning
confidence: 99%